2010
DOI: 10.1134/s1054660x10110046
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of thermal changes in human teeth during photodynamic antimicrobial chemotherapy performed with red light sources

Abstract: Photo disinfection of deep dentin caries lesions may be a useful tool for preserving tooth struc ture. However, increase of pulpal temperature higher than 5.5°C may put pulp vitality in danger. Objectives: This in vitro study evaluated thermal effects of radiation of the red spectrum (λ = 600-700 nm, 94 J cm-2) on pulpal and periodontal areas when irradiating deep dentin cavities in human teeth. Methods: Tooth prep aration was performed at occlusal surface in 10 human teeth, which were irradiated by five diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Most studies investigating the antibacterial effect of TBO-mediated aPDT against cariogenic pathogen employed LED as it produces a low power output, which is beneficial to not causing damage to adjacent tissues, and reduced cost compared to red lasers [ 25 , 32 ]. Another factor favoring LED use is its classification as non-coherent light presetting an amplitude in emitted light waves [ 35 ]. The LED chosen for this study presents a bandgap of 8 nm that overlaps the absorption band of TBO.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies investigating the antibacterial effect of TBO-mediated aPDT against cariogenic pathogen employed LED as it produces a low power output, which is beneficial to not causing damage to adjacent tissues, and reduced cost compared to red lasers [ 25 , 32 ]. Another factor favoring LED use is its classification as non-coherent light presetting an amplitude in emitted light waves [ 35 ]. The LED chosen for this study presents a bandgap of 8 nm that overlaps the absorption band of TBO.…”
Section: Discussionmentioning
confidence: 99%
“…The external electrode presented a higher temperature variance within the safe spectrum until 22 sec, which indicates that a highpower output may be an important factor in temperature increase even when using the same energy density. 22 Further, temperature changes in vitro are possibly higher than those in vivo, considering that in this in vitro model, no oral tissue was available to dissipate the heat. In a clinical situation, temperature is balanced by the movement of fluids in the dentinal tubules and blood circulating in the pulp chamber.…”
Section: Discussionmentioning
confidence: 95%
“…In this scenario, it is known that different stimuli such as temperature might affect negatively the physiology of the interaction between pulp and dentin. 22 When the use of lasers for caries prevention and treatment was first studied, researchers concluded that the technology was impractical due to the heat generated at the application site and the consequent cracking and distortion of the enamel. 23 Currently, a more detailed understanding of the mechanics of hard tissue ablation is available, and lasers that are effective on the absorbing components of the tissue have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…LED curing units have been reported to generate less heat than laser [40] and diode lasers can show a similar effect [23]. De-Paula et al [30] highlighted that temperature is lower when low output power lasers at 0.5-50.0 mW are used than when high output power are used.…”
Section: Discussionmentioning
confidence: 96%
“…For this, a K-type thermocouple (wire diameter of 0.25 mm) was coupled to a digital portable thermometer (model MT 600; Minipa, São Paulo, SP, Brazil) with Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 6/25/15 5:17 AM a resolution of 0.1°C, a basic precision of 0.1 ± 0.7%, and with a temperature range from 0.1 to 200°C. The thermocouple wire was connected to a data logger (Temp Monitor Software; Minipa, Sao Paulo, SP, Brazil) and the mean of the difference between the baseline and the highest temperature was calculated for each specimen (ΔT parameter) and each group [30].…”
Section: Temperature Measurementmentioning
confidence: 99%